2008
DOI: 10.1038/bjp.2008.98
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy: novel third‐generation photosensitizers one step closer?

Abstract: Photodynamic sensitizers are drugs activated by light of a specific wavelength and are used in the photodynamic therapy (PDT) of certain diseases. Second-and third-generation photosensitizers with improved PDT properties are now under investigation. In this issue of the British Journal of Pharmacology, Leung et al. have described the synthesis and investigation of a second-generation photosensitizer (BAM-SiPc) targeted towards the cells of HepG2 and HT29 tumours. BAM-SiPc is selectively functionalized with bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
131
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(135 citation statements)
references
References 12 publications
0
131
0
4
Order By: Relevance
“…Thus, it became important to develop compounds with improved 'deliverability'. Currently, research on this the third generation of photosensitizers is ongoing and these new drugs are characterized by conjugation to carrier molecules or prodrug-drug conversion steps, both of which specifically target the PS to the target cells, resulting in minimized accumulation in healthy tissues [8]. The development of safe and highly selective photosensitizing agents is the main topic of many ongoing research programs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it became important to develop compounds with improved 'deliverability'. Currently, research on this the third generation of photosensitizers is ongoing and these new drugs are characterized by conjugation to carrier molecules or prodrug-drug conversion steps, both of which specifically target the PS to the target cells, resulting in minimized accumulation in healthy tissues [8]. The development of safe and highly selective photosensitizing agents is the main topic of many ongoing research programs [6].…”
Section: Introductionmentioning
confidence: 99%
“…These ROS are able to oxidize subcellular molecules inducing cellular apoptosis or necrosis (18,23,28). It has also been shown that porphyrins can be incorporated into liposomal delivery systems, diminishing their cytotoxicity without affecting the efficacy of the compounds during photodynamic treatment (17,27).…”
mentioning
confidence: 99%
“…No entanto, o uso da TFD é limitado devido a alguns efeitos indesejáveis, como por exemplo, a fraca especificidade na biodistribuição e ainda na prolongada acumulação do fotossensibilizador em tecidos não-neoplásicos. 9,10 Os fotossensibilizadores de 1ª geração, como o Photofrin®, apesar de serem amplamente usados no tratamento de vários tipos de cânceres ou condições pré-cancerígenas, apresentaram algumas desvantagens. Destas destacam-se a prolongada fotossensibilidade cutânea, a baixa seletividade pelo tecido tumoral e a banda de absorção onde a droga é fotoativada (região do vermelho) é fraca, não se encontrando na região ideal do espectro.…”
Section: Introductionunclassified
“…Além disso, grande parte destes fotossensibilizadores são misturas de composição variável, não tendo sido possível isolar nem caracterizar a principal substância ativa. 9,13,14,16 Alguns destes fotossensibilizadores de 2ª geração são derivados de porfirinas reduzidas (clorinas, bacterioclorinas), benzoporfirinas, ftalocianinas e naftalocianinas. Estas são substâncias que apresentam algumas propriedades fotofísicas desejáveis, como é o caso das clorinas e as bacterioclorinas com uma banda de absorção intensa entre 660-690 nm e 730 nm, respectivamente; as ftalocianinas e naftalocianinas apresentam uma banda intensa entre 670 nm e 820 nm e as benzoporfirinas que apresentam grande aptidão para se localizarem rapidamente nas células neoplásicas.…”
Section: Introductionunclassified